Development of Da'i Competency Model in Campus Using Psychological and Management Approach - Hasyim Hasanah; Ibnu Hadjar; Baidi Bukhori (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2018)
The success of da’wah in campus is determined by level of da’wah competency of its cadre, so that it needs to be developed. This study is intended to answer the problem (1) how is the development of competencies campus cadre da’i? (2) what are the factors affecting the development cadre of the competencies? (3) How is the models development of competence using psychological and management approach? The discussion is based on a literature review using a psychological and management approach, so descriptive based on induction and reflection logic. It is concluded that (1) model of competency development of the cadres can be carried out through two models, competency-building models, namely core competencies and distinctive competencies, reflecting five aspects: substantive, methodological, social, spiritual and professional competencies. (2) The development of competence of the cadre is affected by factors such as self-concept, religious conciousness, motivation to da’wa, and environment especially the intensity of joining group guidance. (3) The models of da’wah competency development is indicated by direct theoretical relationship with self-concept, religious conciousness, and motivation to da’wa, and indirect one with the intensity of joining group guidance. Keberhasilan dakwah kampus ditentukan dari tingkat kompetensi para kadernya, sehingga komptentesi tersebut perlu dikembangkan lebih lanjut. Penelitian ini dimaksudkan untuk menjawab masalah (1) Bagaimana pengembangan kompetensi kader da’i? (2) Apa faktor yang memengaruhi kompetensi kader da’i? (3) Bagaimana pengembangan model kompetensi kader da’i dengan pendekatan psikologi dan manajemen? Pembahasan didasarkan pada kajian pustaka dengan menggunakan pendekatan psikologi dan manajemen, serta analisis deskriptif berdasarkan logika induksi dan refleksi. Dari pembahasan dapat disimpulkan bahwa (1) Pengembangan model kompetensi kader da’i dapat dilakukan melalui dua model pembentuk kompetensi, yaitu kompetensi inti dan kompetensi pembeda, yang merefleksikan lima aspek yaitu kompetensi substantif, metodologis, sosial, spiritual, dan profesional. (2) Pengembangan kompetensi kader da’i dipengaruhi faktor khususnya konsep diri, kesadaran beragama, motivasi berdakwah, dan faktor lingkungan seperti intensitas mengikuti bimbingan kelompok. (3) Pengembangan model kompetensi kader da’i ditunjukkan oleh hubungan teoretik secara langsung dangan konsep diri, kesadaran beragama, dan motivasi berdakwah dengan kompetensi kader da’i, dan secara tidak langsung melalui intensitas mengikuti bimbingan kelompok.